PENGARUH PENGUNGKAPAN CORPORATE GOVERNANCE, ENVIRONMENTAL SOCIAL GOVERNANCE, ENVIRONMENTAL UNCERTAINTY DAN CORPORATE REPUTATION TERHADAP TAX AVOIDANCE - Hikmahtul Nurlaely; Rosiyana Dewi (ITB AAS Indonesia Surakarta, 2024)
This study aims to examines and analyze the influence of Corporate Governance disclosure, Environmental Social Governance, Environmental Uncertainty, and Corporate Reputation on Tax Avoidance. The research employed a quantitative approach with secondary data obtained from the annual reports of companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange from 2019 to 2022. The Purposive Sampling method employed in this research yielded 59 company samples, and the study spanned four years, resulting in 236 samples. This study utilized multiple linear regression analysis. The results of this research indicated that Corporate Governance disclosure has a negative influence on Tax Avoidance, Environmental Social Governance has a negative influence on tax avoidance, Corporate Reputation has a negative influence on Tax Avoidance, and Environmental Uncertainty has no influence on Tax Avoidance